Five power defence arrangements at forty - Storey, Ian 1970-; Singh, Daljit; Emmers, Ralf 1974- (Institute of Southeast Asian Studies, 2011)
Established in 1971 by Singapore, Malaysia, Britain, Australia and New Zealand, the Five Power Defence Arrangements (FPDA) has proved to be one of Asia's most enduring military pacts. Since its foundation, the FPDA has functioned as an important confidence building measure between its two Southeast Asian members, and has facilitated interoperability, professionalization and cooperation among the armed forces of the five countries. Crucially, its inherent flexibility and adaptability has enabled it to respond effectively to changes in the geopolitical environment as well as the emergence of new security threats. Now in its fortieth year, the FPDA remains a valuable component of Asia's security architecture in a time of change and uncertainty. This volume marks the fortieth anniversary of the establishment of the FPDA. Regional and international scholars examine the primary motivations of the five members, the FPDA's contribution to regional security over the past four decades and explore possible future roles for the alliance in the context of emerging geopolitical trends and security challenges in the twenty-first century